COMPARISON OF DENOSUMAB AND ALENDRONATE EFFICACY AND RELATED DIABETES RISK IN PATIENTS WITH OSTEOPOROSIS - Ismail, Noor Ashikin; Hadil, Fatin Aziera; Mohamad, Masni (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Osteoporosis and diabetes mellitus are highly prevalent among postmenopausal women and the elderly in Malaysia. Recent studies have suggested blocking the RANK ligand may improve glucose metabolism and delay the development of diabetes. METHODOLOGY We compared the efficacy of denosumab with alendronate in treating osteoporosis and examined the potential reduction of the risk of diabetes in each treatment group. RESULTS This is a cross-sectional analysis of patients over 40 years old who received osteoporosis treatment with denosumab and alendronate for more than a year at Putrajaya Hospital. Independent t-test and Pearson’s chi-square were used to examine associations between continuous and categorical variables. A total of 182 patients were included (mean [SD] age, 71.2 [10] years; 170 [93%] female). The majority were of Malay descent (47%) followed by Chinese (32%) and Indian (20%). Hypertension was the most common comorbidity (63%) followed by dyslipidaemia (48%), diabetes (29%) and prediabetes (15%). Majority with previous osteoporosis fractures received denosumab (54%) versus alendronate (44%). The denosumab group showed significant improvements in bone strength (p <0.01) mainly at the lumbar spine compared to the alendronate group. Patients who developed diabetes were numerically lower in the denosumab group compared to the alendronate group, 53% vs 63%, respectively, with an OR of 0.688 (95%CI, 0.34 – 1.39). CONCLUSION These findings highlight significant improvements in BMD with the use of denosumab compared to alendronate, particularly at the lumbar spine. Additional prospective studies are needed to establish the role of denosumab in lowering diabetes risk in osteoporosis patients.